Synthesis and characterization of monodisperse uniformly shaped respirable aerosols. Issue 9 (25th June 2013) - Fromen, Catherine A.; Shen, Tammy W.; Larus, Abigail E.; Mack, Peter; Maynor, Benjamin W.; Luft, J. Christopher; DeSimone, Joseph M.
<x xml:space="preserve">Abstract</x> The top‐down, micromolding technique, referred to as Particle Replication in Nonwetting Templates (PRINT®), affords a new opportunity for the generation of inhalation therapeutics. Powders were fabricated with predetermined particle size and shape; when dispersed with a collision jet nebulizer, these particles resulted in monodisperse aerosols with geometric standard deviations well below 1.2. Dynamic shape factors for this novel set of uniformly shaped particles were determined by correcting the drag of nonspherical particles in the ultra‐Stokesian flow conditions of the aerodynamic particle sizer (APS). This convenient approach for shape factor determination agreed well with current literature approaches and allowed for the correction of APS results for particles with known volumes. Determined shape factor values of PRINT geometries were used to estimate the theoretical median aerodynamic diameters of individual aerosols, which were then compared to actual inhalation powders. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3184–3194, 2013